Linguistic gentrification: The Baptist Missionary Society and Bobangi (1882-1940) - Michael, Meeuwis (AAeO - Afrikanistik-Aegyptologie-Online, 2023)
This is a study of how, between 1882 and roughly 1940, missionaries of the Baptist Missionary Society (BMS) working on the left bank of the western sections of the Congo River “engaged” and “engaged with” the Bantu language Bobangi. It traces the ways in which and the reasons why, for their missionary and school work, they decided to turn to, and later away from, Bobangi. It addresses the changes the motives and linguistic ideologies behind these choices went through, as well as the doubts, disagreements, and conflicts visible in the BMS’s own ranks. In this context, I particularly zoom in on the metalinguistic representations the BMS made of the language, in publications such as John Whitehead’s Grammar and Dictionary of the Bobangi Language of 1899. I suggest the notion of “linguistic gentrification”, i.e. the missionary creation of an “embellished” and “improved” version of the language, which was imposed back onto the native speakers in missionary schools as the new, only correct way of speaking, resulting in the exclusion of these native speakers from their own language – indeed in much the same way as gentrification operates in urbanization.